Estudo clínico-epidemiológico de um surto de infecção da corrente sanguínea por pseudomonas aeruginosa em unidade neonatal de um hospital de ensino - BOULHOSA, Daniele da Costa (2022)
The blood stream represents the most common site for nosocomial infection in Neo-natal Intensive Care Unities (NICUs). Infections by means of gram-negative bacteria outbreaks, as Pseudomonas aeruginosa in NICUs might represent a potential risk to those newborn children, as they are highly susceptible to bacterial infections, contributing to high levels of morbimortality in this population. The present approach studies an outbreak through P. aeruginosa infection in the blood stream (BSI) at the Neonatal Unity of the Fundação Santa Casa de Misercórdia do Pará, from January 2004 to June 2006, aiming to describe its clinic-epidemiological characteristics. A transversal, descriptive-type analysis was performed, based on revision of the medical records of those cases considered as severe, regarding retrospective components. The BSI by P. aeruginosa occurred from January 2004 to October 2005, involving 13 newborns. 61,5% of the studied population presented male phenotype, weighting 1533,1 ± 419,1g with a gestational age of 33,53 ± 2,5 weeks. Empiric antibiotic therapy was preformed over 100% of the studied population. Imipenem-based treatment was observed in 53,8%, and 84,6% was submitted to mechanical aeration. The average time until the rising of the BSI (bacteremia) was 17,53 ± 17,56 days. 30,8% of the observed strains presented multi-resistance to any antibiotic. A 46,2% infection-related mortality rate was observed. The blood stream infections by P. aeruginosa usually occurs lately in premature newborns, submitted to mechanical aeration, also submitted to a high-level antibiotic-therapy, causig the high mortality rates. Also, Multi-resistance rates were observed as well among isolated strains of P. aeruginosa in Neonatal unities.